Penyusunan Anggaran Biaya Tenaga Kerja: Tantangan dan Solusi Untuk Bisnis Berkelanjutan - Muammar Khadafi; Nadiatul Fitri; Fatin Nabila; Suci Ikramina; Raihan Rizq Hamdi Lubis (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Every business requires effort to start thinking about its business. Most businesses have a primary goal of making a profit, but now, they must shift to thinking comprehensively about other aspects beyond profit, namely people. Preparing a cost budget is a crucial component in a sustainable business, because this business does not only focus on financial profits, but also pays attention to social and environmental impacts. Challenges in budgeting for business sustainability include high initial costs for environmentally friendly technologies, measuring non-financial impacts, rapid regulatory changes, and limited resources. This article discusses these challenges and offers practical solutions, such as a phased approach, leveraging government incentives, and collaboration with sustainable partners. With the right strategy in place, businesses can strike a balance between profitability and immortality goals, building a strong foundation for the long term.